Answer:
Step-by-step explanation:
To solve this problem, we need to multiple
and -2 by
and add the results together:
![x(x^{2} + 2x + 4)](https://tex.z-dn.net/?f=x%28x%5E%7B2%7D%20%2B%202x%20%2B%204%29)
![x^{3} + 2x^{2} + 4x](https://tex.z-dn.net/?f=x%5E%7B3%7D%20%2B%202x%5E%7B2%7D%20%2B%204x)
![-2(x^{2} + 2x + 4)](https://tex.z-dn.net/?f=-2%28x%5E%7B2%7D%20%2B%202x%20%2B%204%29)
![-2x^{2} - 4x - 8](https://tex.z-dn.net/?f=-2x%5E%7B2%7D%20-%204x%20-%208)
Adding the two together give the following:
![(x^{3} + 2x^{2} + 4x) + (-2x^{2} - 4x - 8)](https://tex.z-dn.net/?f=%28x%5E%7B3%7D%20%2B%202x%5E%7B2%7D%20%2B%204x%29%20%2B%20%28-2x%5E%7B2%7D%20-%204x%20-%208%29)
![x^{3} - 8](https://tex.z-dn.net/?f=x%5E%7B3%7D%20-%208)
The question here is how long does it take for a falling
person to reach the 90% of this terminal velocity. The computation is:
The terminal velocity vt fulfills v'=0. Therefore vt=g/c,
and so c=g/vt = 10/(100*1000/3600) = 36,000/100,000... /s. Incorporating the
differential equation shows that the time needed to reach velocity v is
t= ln [g / (g-c*v)] / c.
With v=.9 vt =.9 g/c,
t = ln [10] /c = 6.4 sec.
Answer:
39
Step-by-step explanation:
Hi,
Work:
Equation;
![11x + 4 + 51 + 2x + 8 = 180](https://tex.z-dn.net/?f=11x%20%2B%204%20%2B%2051%20%2B%202x%20%2B%208%20%3D%20180)
Collect like terms and calculate sum of positive numbers.
![13x + 63 = 180](https://tex.z-dn.net/?f=13x%20%2B%2063%20%3D%20180)
Move constant +63 to the right side and change its sign.
![13x = 180 - 63](https://tex.z-dn.net/?f=13x%20%3D%20180%20-%2063)
Subtract numbers.
![13x = 117](https://tex.z-dn.net/?f=13x%20%3D%20117)
Divide both sides of equation with 13.
![x = 9](https://tex.z-dn.net/?f=x%20%3D%209)
Hope this helps.
r3t40
Answer:
98
Step-by-step explanation:
Of means multiply
70% * 140
.70 * 140
98